ChemInform Abstract: An Efficient One‐Pot Synthesis of 2‐Bromo‐6‐aryl[5H]pyrrolo[2, 3‐b]pyrazines. Issue 29 (July 2015) - Simpson, Iain; St‐Gallay, Steve A.; Stokes, Stephen; Whittaker, David T. E.; Wiewiora, Rafal
Abstract A new two step one‐pot method for the synthesis of the title compounds is described.